The institutional educational project and its relationship with the quality educational management of Educational Institution Antenor Orrego Espinoza, San Juan de Lurigancho - Lima - Vicente Fernández, Dilcia María (2019)
The present research has a general objective to determine the relation that exists between the Institutional Educational Project with the Educational Quality Management. It is a research that belongs to the type of basic study because its results enrich the scientific knowledge in education. It is descriptive level and assumes the correlational design because it establishes a relationship between two variables: Institutional Educational Project and Quality Educational Management. The sample consisted of 165 people: 3 managers, 3 administrative and/ or personal staff, 11 teachers at the primary level, 16 teachers at the secondary level, 66 students at the 4th level of high school and 66 parents of the students. The sample size was chosen intentionally non-probabilistic.